2020
DOI: 10.2106/jbjs.oa.19.00061
|View full text |Cite
|
Sign up to set email alerts
|

Patient Electronic Health Records Score for Preoperative Risk Assessment Before Total Knee Arthroplasty

Abstract: Background: Current preoperative risk assessment tools are often cumbersome, have limited accuracy, and are poorly adopted. The Care Assessment Need (CAN) score, an existing tool developed for primary care providers in the U.S. Veterans Administration health-care system (VA), is automatically calculated for individual patients using electronic health record data. Therefore, it could present an efficient preoperative risk assessment tool. The aim of this project was to determine if the CAN score ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…The CAN score is a tool that assesses patients' risk of morbidity and mortality using a wide array of data available in the EHR, including socio-demographics, clinical diagnoses, vital signs, medications, lab values, and health care utilization data (S2 Table ). Our previous work has established that the CAN score successfully risk-stratifies COVID-19 patient outcomes with the strongest performance demonstrated in predicting mortality [6,7]. The CAN score ranges from 0 to 99, with a higher score representing a greater risk patient.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…The CAN score is a tool that assesses patients' risk of morbidity and mortality using a wide array of data available in the EHR, including socio-demographics, clinical diagnoses, vital signs, medications, lab values, and health care utilization data (S2 Table ). Our previous work has established that the CAN score successfully risk-stratifies COVID-19 patient outcomes with the strongest performance demonstrated in predicting mortality [6,7]. The CAN score ranges from 0 to 99, with a higher score representing a greater risk patient.…”
Section: Plos Onementioning
confidence: 99%
“…As part of our continual quality improvement and assessment efforts, we have been developing and validating predictive models to optimize care strategies. Our recent work demonstrated that existing electronic health record (EHR) data can be utilized at VA to assess risk in the form of the Care Assessment Needs (CAN) score for different groups of Veterans including those battling COVID-19 [6,7]. In the process of optimizing COVID-19 specific predictive models, we identified a strong correlation between preexisting aspirin prescription and decreased all-cause mortality.…”
Section: Introductionmentioning
confidence: 99%
“…The CAN score is a tool that assesses patients’ risk of morbidity and mortality using a wide array of data available in the EHR, including socio-demographics, clinical diagnoses, vital signs, medications, lab values, and health care utilization data. Our previous work has established that the CAN score successfully risk-stratifies COVID-19 patient outcomes with the strongest performance demonstrated in predicting mortality 6-7 . The CAN score ranges from 0 to 99, with a higher score representing a greater risk patient.…”
Section: Methodsmentioning
confidence: 99%
“…As part of our continual quality improvement efforts, we have been developing and validating predictive models to optimize care strategies. Our recent work demonstrated that existing electronic health record (EHR) data can be utilized at VA to assess risk in the form of the Care Assessment Need (CAN) score for different groups of Veterans including those battling COVID-19 6-7 . In the process of optimizing COVID-19 specific predictive models, we identified a strong correlation between preexisting aspirin prescription and decreased all-cause mortality.…”
Section: Introductionmentioning
confidence: 99%
“…In the latest iteration of the CAN (version 2.5), inpatient Veterans also have CAN mortality models generated [3]. Our recent work has also demonstrated that the CAN score can be repurposed as a presurgical risk assessment tool [4].…”
Section: Introductionmentioning
confidence: 99%